PENGARUH MOTIVASI, DISIPLIN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT. SURYA EKASARI UTAMA - Dewi Kusmayasari; Abdul Hadi; Nurul Fauziyah (J-MACC, 2023)
Motivation, Work Discipline, Leadership Style are variables that affect employee performance. To determine the magnitude of the influence of employee performance, it is done by multiple regression analysis. This study aims to determine the effect of motivation, work discipline, leadership style on employee performance either simultaneously or partially. This study used a sample of 61 respondents. Simultaneous analysis results show that all independent variables, namely motivation, work discipline and leadership style have a significant effect on employee performance. The magnitude of the effect is 0.261 or 26.1%. After the F test, the magnitude of the F-count is 70.321 > F-table 2.09 and the p-value is 0.000 <0.05 and the effect is significant both from the F-test and the significant test. This shows that together the variables of motivation, work discipline and leadership style have an effect on employee performance. It means that there is a simultaneous influence of the variables of Motivation, Work Discipline, and Leadership Style on Employee Performance.